2022
DOI: 10.1038/s41598-021-04653-2
|View full text |Cite
|
Sign up to set email alerts
|

Spatial correlations in geographical spreading of COVID-19 in the United States

Abstract: The global spread of the COVID-19 pandemic has followed complex pathways, largely attributed to the high virus infectivity, human travel patterns, and the implementation of multiple mitigation measures. The resulting geographic patterns describe the evolution of the epidemic and can indicate areas that are at risk of an outbreak. Here, we analyze the spatial correlations of new active cases in the USA at the county level and characterize the extent of these correlations at different times. We show that the epi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…A study from U.S. showed that the correlations between urban centers were significant indicating that spreading was facilitated by travel between cities. 8) The central part of the city, with heavy commuter as it serves as business district and relatively smaller number of population residing, was shown to have the highest attack rate among all districts, as in line with this finding. Given that the school closure measures were uniformly practiced in all 25 districts in Seoul, our finding suggest that the community-onset SARS-CoV-2 transmission was likely the cause of COVID-19 clusters in student population.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 72%
“…A study from U.S. showed that the correlations between urban centers were significant indicating that spreading was facilitated by travel between cities. 8) The central part of the city, with heavy commuter as it serves as business district and relatively smaller number of population residing, was shown to have the highest attack rate among all districts, as in line with this finding. Given that the school closure measures were uniformly practiced in all 25 districts in Seoul, our finding suggest that the community-onset SARS-CoV-2 transmission was likely the cause of COVID-19 clusters in student population.…”
Section: A C C E P T E D a R T I C L Esupporting
confidence: 72%
“…3,17 These trends mirror timelines previously documented for cancer screening, diagnosis, and treatment, as the health care system was strained in the early days of the pandemic. [6][7][8]16,18,19 Temporal geographic variation in pandemic spread has been well documented 20,21 and significant variance in geographic distribution of cancer cases in the NCDB was noted in 2020.…”
Section: Discussionmentioning
confidence: 99%
“…McLafferty (2010) suggests that geographically close countries are likely to share spatio-temporal dynamics due to human spatial dynamics and similar demographic factors across geographic regions. In reviewing the available literature, McMahon et al (2022) highlight that a country's interconnectedness influences the spreading dynamics of Covid-19. This literature suggests that geographical closeness and interconnectivity have substantial implications for the spreading dynamics of Covid-19, allowing this to be a potential explanation for the spatial autocorrelation identified in the complexity of spreading dynamics observed in the analysis.…”
Section: Resultsmentioning
confidence: 99%